Cyberbullying Against Women in the News Coverage of Bangladeshi News Media - Hossain , Md.Belal (Bodhi: An Interdisciplinary Journal, 2024)
This study aims to analyze the news regarding cyberbullying against women on the Facebook pages of news media in Bangladesh. Content analysis was used as a method, while media framing was the theory of the study. A total of sixty news stories were selected from the Facebook pages of the Daily Prothom Alo, The Daily Star, Jamuna Television, Somoy Television, Bdnews24.com, and NewsBangla24.com through purposive sampling techniques. The study revealed that most of the news stories (60 percent) were viewed as unfavorable to the victims of cyberbullying. Around 40 percent were treated as straight-jacket news with text-based and video programs. Approximately 25 percent were entertainment and 20 percent were criminal issues with celebrity actresses and police officials as sources of the news stories, respectively. The findings might play a precious role for the policymakers in identifying the victims of cyberbullying, particularly against women, and in making suitable policies for the news media of Bangladesh.